Design and Fabrication of Pneumatic Gear Shifting Mechanism for Two Wheeler - R. , Hariharan; R.J. , Golden Renjith (International Journal of Psychosocial Rehabilitation, 2019)
In this project, we have a tendency to design a gear shift mechanism and applied it to a bicycle with a clutch, dashing up the forwarding method and reducing the disorder of the motive force exploitation the button style. The designed gear makes operation easier and provides economical operation. This new device is reliable, tiny in size, cost-efficient and cheap to keep up. Follow the projected shift technique. The gas switch may be automation that uses compressed gas to modify gears from the clutch next to the motive force to the engine of the vehicle. Gas switches should be thought-about as safety devices. There’s no delay once shifting gears occurring within the clutch and fixing different components of the vehicle.